Economic Contemplations of Sura Quraish - Shadi Anwar Karim Alshawaki (Zanco Journal of Humanity Sciences)
Praise be to Allah, Lord of the Worlds, and prayers and peace be upon our Prophet Muhammad and his family and companions.